Kosa Kata Baru dalam Bahasa Indonesia (Analisis Peneliti Terdahulu Menggunakan Kajian Kualitatif dalam Penggunaan Kosakata Baru Menjadi Bahasa Baku) - Santi Devi (Lembaga Pengembangan Kinerja Dosen, 2023)
Changes in the meaning of words can occur because of the need to accommodate a concept that does not yet have a vocabulary or a concept that has the same component of meaning as a vocabulary that already existed. For example, the use of the word broadcast 'spread'. Originally the meaning of the word broadcast was synonymous with the function of radio, but now it is also used to define other transmissions such as broadcasting counterfeit money. The development of the vocabulary of a language can also show the socio-cultural development of its speakers. This development is unlimited: it will always develop as long as the speakers are still there and use Indonesian in everyday life.